Why Would I Share? Exploring a Culture of Sharing and Collaboration in Canadian Academic Library Instruction - Gill, Navroop (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2023)
Cultures of sharing and collaboration are essential to supporting instruction practices, yet there is limited literature on how these cultures are successfully cultivated in libraries. In this paper, I explore cultures of sharing and collaboration among instruction librarians in Canadian academic libraries. I report on a series of semi-structured interviews (n=14) I conducted with librarians who support or provide information literacy at their institutions. The interview data was reviewed using a thematic analysis approach (Braun and Clark 2022) and coded in NVivo. I explore the barriers and supports to sharing and collaboration as documented in the interviews. Barriers include a) instructional silos caused by the liaison model; (b) a lack of trust in sharing one’s teaching with colleagues; (c) the lack of prioritizing instruction in institutions; and (d) limited time to engage in collaborative work. The supports for sharing and collaboration include (a) intentionally building personal relationships, (b) developing a structure for sharing, and (c) having dedicated time for collaborative work. Based on these findings, practical ways sharing and collaboration can be cultivated in libraries will be explored.